2017
DOI: 10.1016/j.cegh.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of communication disorders in a group of islands in India

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…This finding is in dissonance with those done in other areas of India, such as Lakshadweep, Karnataka, Gujarat etc. 11,12,14…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is in dissonance with those done in other areas of India, such as Lakshadweep, Karnataka, Gujarat etc. 11,12,14…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the literature. 11,12,14 Studies also reported that as the age increases young children outgrow their communication difficulties and improve in their speech and language skills. 31…”
Section: Speech and Language Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference across regions could be due to a variety of reasons like cultural differences, 12 lifestyle, 13 habits, literacy rates, 14 economic status, living conditions (urban vs rural), and geographical location, including availability and access to health care. Understanding these factors and their influence on communication disorders is important to help contribute to the overall development of the country and improve the quality of life of persons with communication disorders.…”
Section: Introductionmentioning
confidence: 99%